Sarcopenia e deglutição em pacientes pós-covid-19 - Berni, Viviane Bohrer (2022)
COVID-19 is a respiratory disease of multisystemic nature, caused by the new coronavirus, SARS-CoV-2, which can be asymptomatic or manifest as mild to severe symptoms. In more severe cases, marked by protein hypercatabolism and prolonged physical inactivity, musculoskeletal repercussions with loss of strength, muscle mass and impaired swallowing function are expected after admission to the Intensive Care Unit. The aim of this study was to investigate and relate the occurrence of sarcopenia and the myoelectric activity of the suprahyoid region of post-COVID-19 patients, stratified by disease severity and sex. This is a cross-sectional and observational study, developed in the Ambulatório de Reabilitação Pós COVID-19 of the Hospital Universitário de Santa Maria (HUSM), RS, in the period from April to September 2021. The sample consisted of 50 patients, of both genders, with a predominant age range between 40 and 59 years, who were admitted to the Unidade de Tratamento Intensivo (UTI) da COVID-19 of the aforementioned hospital. They were stratified into critically ill patients (31 patients), who required only oxygen supplementation at admission, and critically ill patients (19 patients), who required orotracheal intubation and invasive mechanical ventilation. All patients underwent clinical evaluation of swallowing by the Protocolo Fonoaudiológico de Avaliação do Risco de Disfagia (PARD) and electrical activity of the muscles of the suprahyoid region by surface electromyography (EMGs). Peripheral muscle mass and strength were checked by ultrasonography (US), bioimpedance (BIA) and dynamometry, respectively. The critically ill patients showed loss of peripheral muscle strength, with no loss of muscle mass and no change in the myoelectric activity of the suprahyoid region. In the evaluation of the risk of dysphagia, swallowing was classified as normal, for the most part. When considering gender, female patients had lower strength, regardless of the COVID-19 severity classification. Male patients presented loss of mass in both groups. The women in the severe group had higher myoelectric activity of the suprahyoid region at rest, when swallowing pasty and when swallowing liquids. These patients, in the clinical evaluation of swallowing, presented multiple swallowing in the pasty consistency and coughing when swallowing liquids. The correlations between muscle condition and myoelectric activity of the suprahyoid region, considering disease severity and gender, were significant only in the severe group. It was concluded that critically ill male patients had sarcopenia, while female patients had pre-sarcopenia. The relationship between muscle condition and myoelectric activity in the suprahyoid region was evidenced only in the severe group, suggestig that COVID-19 can compromisse the muscles involved in swallowing even in noncritical patients. Thus, the evaluation of such aspects in post-COVID-19 patients is of paramount importance to implemente rehabilitation and restore functionality after hospital discharge.